열처리를 통한 제올라이트 박막 코팅 시 바인더의 영향 - 유영석(Young-Seok Yoo); 조준호(Jun-Ho Jo); 김이태(I-Tae Kim) (Biuletyn Uniejowski, 2013)
This study is an experimental attempt to confirm the binder effect of zeolite coating on glass plate by heat treatment. As a result, zeolite was successfully formed with low concentratios of pressure, whose concentration was effective in 10% or more for thin film zeolite coating. And as the content of the binder (TEOS) in mixed coating solution was higher, the zeolite was fastened better on the surface. Above 5% content of the binder in the coating solution, TEOS hindered zeolite synthesis of the precursor and brought to zeolite capacity decrease. Furthermore, when the concentration of the precursor, sedimentation rate of the precursor was higher and the coating efficiency is reduced thereby. Therefore, the most effective concentrations of the precursor and TEOS in the coating solution was 10% and 5%, respectively. It was concluded that zeolite coating is produced by heat treatment method after dipping without hydrothermal synthesis.